177 Camrelizumab combined with apatinib for refractory gestational trophoblastic neoplasia: A phase 2, single-arm, prospective Study. (13th November 2020) - Cheng, H; Yang, J; Zhao, J; Wan, X; Xiang, Y
Abstract : Objective: To assess the safety and efficacy of camrelizumab and apatinib as combination therapy in patients with refractory gestational trophoblastic neoplasia (GTN). Methods: In this open-label, single-arm, phase 2 study, eligible participants were diagnosed with recurrent/chemoresistant high-risk GTN previously received twice or more combination chemotherapy. Patients received intravenous camrelizumab 200 mg every 2 weeks and apatinib 250 mg orally taken once daily. The primary outcome was objective response rate and the secondary outcomes included safety, and one year of duration of response, and disease free survival. Results: Between Aug 7, 2019, and March 18, 2020, 20 patients were enrolled. At data cut-off (May 20, 2020), all patients were able to evaluate for efficacy. The most common adverse event (AE) of any grade is neutropenia (8 [40%] patients). Grade 3/4 treatment-related AEs occurred in 60% (12/20) of the patients, and the grade 3/4 AEs included hypertension (5 [25%] patients), rash (4 [20%] patients), leukocytopenia (2 [10%] patients), elevated transaminase (2 [10%] patients), neutropenia (1 [5%] patient), and hand-foot syndrome (1 [5%] patient). One patient had treatment-related serious AE. No treatment-related death occurred in this trial. The objective response rate was 55% (11/20), and complete response rate and partial response rate was achieved in 35% (7/20) and 20% (4/20), respectively. The median progression-free survival and duration of response has not been reached. Conclusion: The combination of camrelizumab and apatinib demonstrated tolerable toxicity and showed encouraging activity in patients with refractory GTN. Larger clinical trials of predictive biomarkers of response are needed.